2004
DOI: 10.1074/jbc.m402913200
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Structure of Wza, the Protein Required for Translocation of Group 1 Capsular Polysaccharide across the Outer Membrane of Escherichia coli

Abstract: Wza is a highly conserved multimeric outer membrane protein complex required for the surface expression of the serotype K30 group 1 capsular polysaccharide in Escherichia coli. Here we present the first three-dimensional structure of this type of polysaccharide exporter at a 15.5-Å resolution obtained using single particle averaging on a dataset of cryo-negatively stained protein.Previous structural studies on purified Wza have revealed a homo-oligomeric ring structure that is most probably composed of eight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…However, SypC differs in size from other Wza proteins (full-length SypC is 703 amino acids in length, whereas Wza proteins from E. coli and Vibrio vulnificus are only 379 and 410 amino acids, respectively), suggesting that it may also carry out an additional function. Both the E. coli and V. fischeri proteins have or appear to have a signal peptide that would direct them across the inner membrane, but neither protein has the ␤-barrel structure typical of outer membrane proteins (1). We found that the putative signal sequence was important for SypC function, as the deletion of the N terminus abrogated the function of SypC.…”
Section: Discussionmentioning
confidence: 68%
“…However, SypC differs in size from other Wza proteins (full-length SypC is 703 amino acids in length, whereas Wza proteins from E. coli and Vibrio vulnificus are only 379 and 410 amino acids, respectively), suggesting that it may also carry out an additional function. Both the E. coli and V. fischeri proteins have or appear to have a signal peptide that would direct them across the inner membrane, but neither protein has the ␤-barrel structure typical of outer membrane proteins (1). We found that the putative signal sequence was important for SypC function, as the deletion of the N terminus abrogated the function of SypC.…”
Section: Discussionmentioning
confidence: 68%
“…Such quasi-symmetry is well characterized for viral capsids, but has been described relatively infrequently outside this group of structures. We note, however, that quasi-symmetry is a feature of some other membrane protein structures, including the EmrE homodimer (36), the BetP trimer (37), the polysaccharide K antigen transporter Wza (38), and also the membrane-associated "adaptor" protein PspA (39). There is also evidence that the quaternary structure of the PapC usher involves quasi-symmetry (40).…”
Section: Discussionmentioning
confidence: 99%
“…The images suggested Wza to be a channel-forming protein (28,79). Subsequent single-particle analyses of Wza oligomers visualized by cryo-negative-staining EM (15.5-Å resolution), revealed a novel hollow, barrel-like structure (dimensions, 90 by 90 by 100 Å) (10). The unique features of Wza were reinforced with a 2.3-Å-resolution crystal structure (26).…”
Section: Wza the Efflux Channel For E Coli Group 1 Cps: The Prototymentioning
confidence: 94%